(untitled) - Krotee, March L. (Boston, 2007)
This book offers a solid foundation of management concepts, skills, and techniques that enable students to develop and test the leadership, decision-making, and problem-solving required for their role in the profession of physical education and sport. The thirteenth edition continues to focus on the management and administration of physical education, sport, and recreational programs in educational settings, as well as in the public and private domains.
Keywords: Physical education and training,Sports administration; Administration